Psychometric evaluation of the reminiscence functions scale in the Malay language for older adults - Thiyagarajan, Ahsha Vaksalla; Ching, Sin Siau; Ibrahim, Norhayati; Amit, Noh; Ghazali, Shazli Ezzat; Syed Elias, Sharifah Munirah; Subramaniam, Ponnusamy (Universiti Kebangsaan Malaysia, 2025)
The Reminiscence Functions Scale (RFS) is a commonly used survey instrument to assess psychological well-being among older adults. The study aims to examine the validity and reliability of the RFS in the Malay language. The RFS was back-translated into the Malay language by two independent linguistic experts, and modified by two clinical psychologists. Principal Axis Factoring examined the factor structure of the translated scale. Convergent validity was determined by correlating the scale with the Satisfaction with Life Scale (SWLS). Cronbach’s alpha determined the internal consistency reliability. A total of 173 older adults (mean age = 69.3, SD = 6.64) participated. After the deletion of items with problematic communality and item loading values, a final 17- item scale was tested. Principal axis factoring extracted four factors explaining 66.9% of the total variance. The Cronbach’s alpha for the scale score was excellent (0.907), and good for its subscales (Factor 1 = 0.885, Factor 2 = 0.877, Factor 3 = 0.836, and Factor 4 = 0.793). The Malay RFS and its subscales significantly correlated with satisfaction with life, except the Bitterness Revival subscale. The results suggest that a 17-item Malay RFS with a four-factor solution has acceptable psychometric properties.